Nanocurcumin Preparation for Reducing Vcam-1 and IL-6 in High Fat Diet-Induced Hyperlipidemic Rats - Dimas Adhi Pradana; Maulana Ardhi; Arifa Caryn Dea Utami Hasyono; Dzihni Meytasari; Farah Deastasa Nabilah; Rochmy Istikharah; Lutfi Chabib (Indonesian Journal of Pharmacy, 2019)
Hyperlipidemia is a pathological condition due to lipid metabolism abnormalities. Increased and oxidized LDL in hyperlipidemia will trigger an inflammatory response and produce proinflammatory cytokines, such as vascular cell adhesion molecule-1 (VCAM-1) and Interleukin-6 (IL-6). Curcumin can be used as antioxidants, anti-inflammatory and antihyperlipidemia, but as it is practically insoluble in water, formulation of curcumin nanosuspension is made to improve the effects of curcumin therapy. This study was conducted to determine the activities of nanocurcumin preparation as preventive measures for rats induced with hyperlipidemia. The test animals used were 49 male Wistar rats divided into 7 test groups: normal control group, negative control group, 80mg/kg BW/day curcumin control group, and nanosuspension curcumin dose of 80mg/kg BW/day, nanoemulsion curcumin dose of 80mg/kg BW/day, SNEDDS curcumin dose of 80mg/kg BW/day and solid lipid nanoparticles dose of 80mg/kg BW/day. Provision of preventive measure was performed on days 1-67. On day 11-67, the induction of lard and egg yolk (1:1) was administered with a volume of 2mL/200g of rat BW. On the 68th day, blood samples were taken for the determination of VCAM-1 and IL-6 parameters using Biotin-Streptavidin-Amplified Enzyme-Linked Immuno-sorbent Assay method. Data analysis of VCAM-1 and IL-6 levels between test groups were conducted by means of normality test and One-way ANOVA (p<0.05). Based on the data of VCAM-1 and IL-6 levels, nanocurcumin dose of 80mg/kg BW preparation was able to significantly improve the preventive activity of curcumin compared to curcumin suspension dose of 80mg/kg BW by reducing VCAM-1 levels in SNEDDS (53.260%), nanoemulsion (52.737%), nanosuspension (52.325%) and solid lipid nanoparticles (51.444%) and decreasing IL-6 levels in SNEDDS (33.030%), nanoemulsion (31.568%), nanosuspension (29.898%), and solid lipid nanoparticles (28.875%).